2019
DOI: 10.1073/pnas.1807983116
|View full text |Cite
|
Sign up to set email alerts
|

Neuromelanin-sensitive MRI as a noninvasive proxy measure of dopamine function in the human brain

Abstract: Neuromelanin-sensitive MRI (NM-MRI) purports to detect the content of neuromelanin (NM), a product of dopamine metabolism that accumulates with age in dopamine neurons of the substantia nigra (SN). Interindividual variability in dopamine function may result in varying levels of NM accumulation in the SN; however, the ability of NM-MRI to measure dopamine function in nonneurodegenerative conditions has not been established. Here, we validated that NM-MRI signal intensity in postmortem midbrain specimens correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
236
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 167 publications
(251 citation statements)
references
References 80 publications
(142 reference statements)
12
236
1
2
Order By: Relevance
“…Nowadays,t he availability of 7T scanners has increased and anumber of MRI studies of NM in LC have been reported. [183] This shows that MRI of NM is ar eliable marker of NM concentration, which in turn is am arker of CA neuron number. [51] As shown in Section 6, the Fe sites are heterogeneous in NM of SN and only am inor fraction of mononuclear iron(III) is EPR detectable at low temperature,a lthough also the EPR-silent Fe clusters may access excited paramagnetic states at physiological temperature and hence contribute to MRI signal amplification.…”
Section: Magnetic Resonance Imaging Of Neuromelanin As Anew Tool Formentioning
confidence: 93%
“…Nowadays,t he availability of 7T scanners has increased and anumber of MRI studies of NM in LC have been reported. [183] This shows that MRI of NM is ar eliable marker of NM concentration, which in turn is am arker of CA neuron number. [51] As shown in Section 6, the Fe sites are heterogeneous in NM of SN and only am inor fraction of mononuclear iron(III) is EPR detectable at low temperature,a lthough also the EPR-silent Fe clusters may access excited paramagnetic states at physiological temperature and hence contribute to MRI signal amplification.…”
Section: Magnetic Resonance Imaging Of Neuromelanin As Anew Tool Formentioning
confidence: 93%
“…High LC signal may be induced by abundant, intracellular water protons interacting with neuromelanin and other paramagnetic ions not associated with neuromelanin . However, histological studies in humans have consistently demonstrated a close correlation between neuromelanin concentration and T1 neuromelanin‐sensitive MRI intensity in substantia nigra and in LC . Furthermore, in substantia nigra, neuromelanin MRI hyperintensity was correlated to dopaminergic neurons activity as measured by PET …”
Section: Discussionmentioning
confidence: 99%
“…17 However, histological studies in humans have consistently demonstrated a close correlation between neuromelanin concentration and T1 neuromelanin-sensitive MRI intensity in substantia nigra and in LC. 15,22,23 Furthermore, in substantia nigra, neuromelanin MRI hyperintensity was correlated to dopaminergic neurons activity as measured by PET. 23 The segmentation of LC was challenging, as LC is a very small brainstem nucleus, close to the fourth ventricle and surrounded by partial volume artifacts on MRI.…”
Section: To the Best Of Our Knowledge This Is The First Study Comparmentioning
confidence: 92%
See 1 more Smart Citation
“…[24] Angewandte Chemie Aufsätze 8. [183] MRTv on NM ist ein zuverlässiger Marker fürd ie NM-Konzentration und diese wiederum ein Marker fürdie Zahl der CA-Neuronen. [177]).…”
Section: Angewandte Chemieunclassified